Common ancestry of Escherichia coli pyruvate oxidase and the acetohydroxy acid synthases of the branched-chain amino acid biosynthetic pathway. - Chang, Y Y (1988)
A number of enzymes require flavin for their catalytic activity, although the reaction catalyzed involves no redox reaction. The best studied of these enigmatic nonredox flavoproteins are the acetohydroxy acid synthases (AHAS), which catalyze early steps in the synthesis of branched-chain amino acids in bacteria, yeasts, and plants. Previously, work from our laboratory showed strong amino acid sequence homology between these enzymes and Escherichia coli pyruvate oxidase, a classical flavoprotein dehydrogenase that catalyzes the decarboxylation of pyruvate to acetate. We have now shown this homology (i) to also be present in the DNA sequences and (ii) to represent functional homology in that pyruvate oxidase has AHAS activity and a protein consisting of the amino-terminal half of pyruvate oxidase and the carboxy-terminal half of E. coli AHAS I allows native E. coli AHAS I to function without added flavin. The hybrid protein contains tightly bound flavin, which is essential for the flavin substitution activity. These data, together with the sequence homologies and identical cofactors and substrates, led us to propose that the AHAS enzymes are descended from pyruvate oxidase (or a similar protein) and, thus, that the flavin requirement of the AHAS enzymes is a vestigial remnant, which may have been conserved to play a structural rather than a chemical function.